Design of a Semi Automatic Cilantro, Grinder Sifter and Weighing Equipment - Guslita, Marsha; Paramytha, Nina (SITEKIN: Jurnal Sains, Teknologi dan Industri, 2023)
There are so many spices in Indonesia with a variety of ones, one of which is coriander. Coriander is necessary in the kitchen and the world of health, one of Indonesia's most widely used spices. There are two types, namely coarse coriander and powdered/fine coriander. Coriander grinding, sieving, and weighing tools are expected to make it easier for small industries to produce powdered/fine coriander more efficiently and well so that it can affect the pace of economic development. This study aims to discover how to make grinding, sieving, and weighing tools and how they work, assisting small industries in the production of powdered/fine coriander more efficiently and nicely. The measurement results on this tool have good values so that the device can work properly and accordingly. The grinding to weighing process has a different period according to the desired weight. 1 gram can take time from the range of 20-40 seconds